An exploratory field study into schoolgirl pregnancies, with emphasis on the role the school can play in their prevention - Kooverjee, Ishwar (Rhodes University, Faculty of Education, Department of Education, 1992)
This piece of research explores the problem of schoolgirl pregnancies and suggests a role which the school might play in their prevention. Concern over the growing number of unplanned pregnancies under the age of eighteen years at the author's school, culminated in the .present study. Experts on the subject often perceive the problem to be self-defeating to the young girls, medically contra-indicated and socially disruptive. The purpose of this investigation was to determine attitudes towards the description of the problem, to identify causative factors predisposing to pregnancy, and to obtain views on how the school can reconcile efforts to address the problem. The relevant research data was obtained through a comprehensive 64 item attitudinal and knowledge-base questionnaire which was administered to a sample of 187 subjects. The sample comprised seven different occupational groups namely, senior schoolgirls, parents of senior schoolgirls, ex-schoolgirl primigravidae, parents of ex-schoolgirl primigravidae, school teachers, members of the clergy and various health care professionals. The appendices contain full statistical tables as well as full responses to the open-ended essay based on the research questionnaire so that the reader is free to check the reasonableness of the conclusions drawn. In the final chapter the author provides a brief summary of findings, offers justification why the teaching of sex education should be a priority in public schools, and makes recommendations, in the main, for the inclusion of school-based sex education as a component of Guidance in terms of rationale and implementation. In addition, suggestions are made with regard to school policy formulation and networking with parents and other community resources. Finally, a choice of four current model programmes for sex education are proposed in an effort to improve and build upon existing programmes in the present South African curriculum. It is the author's belief that this investigation may contribute to course design and perhaps provide hypotheses for more specific studies in the future.
Keywords: Teenage pregnancy -- South Africa; Sex instruction -- South Africa